(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Glutaric aciduria type 1 (GA-1) is an autosomal recessive rare neurometabolic disorder caused by absent or deficient activity of glutaryl- CoA dehydrogenase. Patient with gluteric aciduria are more likely to develop collection in the subdural space secondary to cerebral atrophy and expansion of CSF spaces. A 1 year and 10 months toddler presented with increased head circumference since birth and generalized seizure for last few days. Neuroimaging showed bilateral subdural collection of CSF intensity. Bilateral subdural peritoneal shunt was inserted. With early diagnosis and adequate treatment , the majority of children with gluteric aciduria type-I are able to live normal. However treatment for gluteric aciduria type-I must be continued for life to avoid lifethreatening complications Bang. J Neurosurgery 2024; 13(2): 162-164